2019
DOI: 10.18502/ijpa.v14i2.1137
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotyping of Trichomonas vaginalis Infected to dsRNA Virus by PCR–Restriction Fragment Length Poly-morphism (RFLP)

Abstract: Background: Trichomonas vaginalis is a prevalent sexually transmitted infection cause trichomoniasis. In this study prevalence and genotype of Iranian isolates of T. vaginalis infected (dsRNA) viruses were evaluated by PCR-RFLP and obtained patterns were then confirmed by sequence analysis and genotype of these Iranian isolates confirmed again. Methods: Ten strains of T.vaginalis were collected from 1700 vaginal samples of women referred to hospitals associated with Iran University of Medical Sciences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We discovered that the clinical samples of T. vaginalis were genotyped E, M or N. In some previous studies, genotypes E and G were reported as the most prevalent, but they were detected in both TVV and TVV −/− samples, while the distribution of virus-carrying strains in the phylogenetic tree was random and not in the same cluster. This suggests that TVV may infect virus-free strains and that there is no relationship between the presence or absence of virus in the parasite and the genealogical status of the parasite [ 31 ]. In addition, we found a strain of T. vaginalis carrying the virus, which implied that the treatment and control of this T. vaginalis strain may be more difficult than those of the T. vaginalis -only strain.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that the clinical samples of T. vaginalis were genotyped E, M or N. In some previous studies, genotypes E and G were reported as the most prevalent, but they were detected in both TVV and TVV −/− samples, while the distribution of virus-carrying strains in the phylogenetic tree was random and not in the same cluster. This suggests that TVV may infect virus-free strains and that there is no relationship between the presence or absence of virus in the parasite and the genealogical status of the parasite [ 31 ]. In addition, we found a strain of T. vaginalis carrying the virus, which implied that the treatment and control of this T. vaginalis strain may be more difficult than those of the T. vaginalis -only strain.…”
Section: Discussionmentioning
confidence: 99%
“…At first, wet mount samples with sterile phosphate-buffered saline(PBS; pH 7.3 ± 0.1) were prepared and observed using light microscope with 10X and then 40X magnification and then another swab was inoculated into a culture tube at 37°C in Diamond’s TYM medium with 10% heat-inactivated calf serum, 100 U/mL penicillin and 30 mg/mL streptomycin sulphate. Finally T.vaginalis culture was harvested in late log phase and centrifuged at 2000 g for 15 min and pellets were stored at −70°C and isolates were confirmed as T.vaginalis by PCR ( 15 , 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…T. vaginalis infection by TVVs could modulate the pathogenicity of T. vaginalis infections by expression of a highly immunogenic T. vaginalis protein, P270 ( 13 ) and also the expression of cysteine proteinases that are assumed to be virulence factors ( 14 ). Genotype of T. vaginalis infected with TVV-1 viruses was evaluated by PCR-RFLP in a study ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…gallinae was reported in Australia [32] , and Europe [33] . Utilizing PCR-RFLP targeting actin gene, three studies were carried out in Turkey [34] , China [31} and Iran [35] . Among twenty T. vaginalis isolates from symptomatic females, genotype E was the most common, followed by G, with only one isolate assigned for H, and two mixed isolates of genotypes E and H [34] .…”
mentioning
confidence: 99%
“…In another report, out of 68 T. vaginalis isolates, two E and H genotypes were found in addition to mixed genotypes in three isolates [31] . Recently, investigators detected three genotypes (E, G and I) in Iranian isolates of T. vaginalis infected with dsRNA viruses [35] . Moreover, the majority of isolates obtained from HIV positive women were parasites from genotype II [28] .…”
mentioning
confidence: 99%